Correction to: Optima nutrition: an allocative efficiency tool to reduce childhood stunting by better targeting of nutrition-related interventions - Ruth Pearson; Madhura Killedar; Janka Petravic; Jakub J. Kakietek; Nick Scott; Kelsey L. Grantham; Robyn M. Stuart; David J. Kedziora; Cliff C. Kerr; Jolene Skordis-Worrall; Meera Shekar; David P. Wilson (BMC, 2018)
It has been highlighted that the original manuscript [1] contains a typesetting error in the name of Meera Shekar. This had been incorrectly captured as Meera Shekhar in the original article which has since been updated.